Analysing the Potential of Blockchain for the Accounting Field in Indonesia - Abdulrival Hartoyo; Eko Ganis Sukoharsono; Yeney Widya Prihatiningtias (Jurnal Akuntansi dan Keuangan, 2021)
This research aims to identify and analyze the potential of blockchain technology for the accounting field in Indonesia. This research was conducted at the Indonesian Blockchain Association. This research uses qualitative methods with the case study approach and analysis of making explanation strategies. The result of this study indicates that blockchain is applicable in Indonesia without having to use cryptocurrency as a payment tool. The result finds that blockchain can be used as a technology for Accounting Information System. One of the reasons is that all accounting transactions have the potential to be traceable with the blockchain. The data in this technology can be considered as relevant information due to the nature of blockchain as a technology that records and stores data that cannot be changed and manipulated. Blockchain will be used as a database and data procession will still be carried out by using the Accounting Information System.  Blockchain is unable to automatically process data into information that may be needed in accounting. This research is expected to strengthen the theory related to blockchain as one of the accounting technologies, also to be an initial step in improving the concept of triple-entry accounting that is usable in Indonesia by using Blockchain which is supported by other platforms such as ERP and uses Token as the representative of assets or financial in recording transactions.